Negotiating End-of-Life Decisions: Entangled Repertoires on the Intermittent Paths of Acute and Palliative Care - Chartrand, Louise (Anthropologica, 2025)
When someone is very ill in Canada, the individual is taken under charge of the medical system and put on one of two distinct paths for handling the situation: either acute or palliative care. In the acute path, all available medical technology is deployed to save lives and avoid death, while the main objective of the palliative path is comfort, as death becomes inevitable and expected. The two paths are ordinarily seen as part of a linear process, wherein acute care is initially deployed and palliative care only after acute care is determined ineffective. In practice, however, the two paths are intermittent, as the reasoning repertoires that guide care practices along both paths are constantly renegotiated by care teams. This article follows the decision-making process regarding the use of the ventilator for two individuals at the end of their lives as their care teams alternate between legal, curing, and care repertoires. The entanglement of these repertoires leads to unexpected care practices as patients are shifted from one path to another. In both cases, the transition from acute to palliative care was nonlinear, and the purposes of the possible medical actions that could be taken along the two paths kept changing as events unfolded.